Assessing Pre-service Science Teachers Conception of Geometric Optics (Transmission of Light) in the Selected Special Science Colleges of Education in Ghana (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of the study was to find out pre-service science teachers conception about geometric optics in the selected Special Science Colleges of Education in Ghana. The study used a fixed non-experimental descriptive survey that went beyond the descriptive to the interpretive in order to provide explanations of patterns and relationships of the results obtained. Five (5) special Science and Mathematics Colleges of Education from five regions in Ghana were selected for the study. Each class was made up of twenty (20) students totalling one hundred (100) students in all. Questionnaire was used to collect data for the study. It was found out that most pre-service science teachers do not understand the practicalities (reflection and refraction) of the aspect of geometrical optics in the physics syllabus they use in teaching. It is recommended that pre-service science teachers should be taken through the practicalities of geometrical optics in the physics syllabus they use in teaching.